The Relationship Between The Use Of Gadgets And Students' Interest In Learning Literatureat Higher Education In Indonesia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims at investigating the effect of gadget on the students’ interest in learning literatureat higher education in Indonesia.This cross-sectional survey used an anonymous onlinequestionnaire to obtain data from participants. Online questionnaire was distributed viaWhatsApp. This is because during Covid-19 pandemic, the teaching – learning process takenplace online. There were 92 participants in the study. The participants in this study were studentsfrom undergraduate degree, majoring Indonesian Language and Literature Study Program at theFaculty of Languages and Literature, State University of Makassar, Makassar, Indonesia. Theonline survey was done on February 2021. The instrument of the study was close-endedquestionnaire consisting of demographic participants and some questions related to onlinelearning practices in the outbreak of Covid-19 pandemic. Quantitative data were analyzed usingdescriptive statistics to present percentage, table, and graphic, and are therefore givencomprehensive explanation and interpretation. Gadget has positive and significant effect on thestudents’ interest in learning literature at higher education.